Rancang Bangun Sistem Monitoring Dan Kontrol Kebocoran Gas Elpiji dengan Mikrokontroler NodeMCU ESP8266 - I Nyoman Gede Adrama; Gilang Ramadhan; I Wayan Sukadana (Universitas Pendidikan Nasional, 2022)
The role of information technology in security is also getting stronger, this is shown by the company's innovation to use technology to support their security equipment. LPG cylinder explosions are usually caused by human error. To minimize human error in the gas installation system, I designed and built a prototype of an LPG gas leak detector with an MQ-2 gas sensor and NodeMCU ESP8266 microcontroller as an input and output controller. The input is an MQ-2 gas sensor and the output is a solenoid valve. The gas sensor detects an increased ambient gas leak odor condition. If the gas odor has exceeded the maximum predetermined limit, the NodeMCU microcontroller will provide an indicator on the panel then send a message to the smartphone via the telegram application and turn off the gas line.